Peran Digitalisasi Dalam Mengoptimalkan Pertumbuhan UMKM Di Desa Pematang Jering Kabupaten Batubara - Nisa, Sofatun; Aisyah, Siti; Azmi, Raisa; Ruslita Batubara, Aisyah Norma; Arief Rahmadiansyah Purba, Muhammad (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
Pematang Jering Village as a Location for KKN Group 15 North Sumatra State Islamic University has MSME businesses, however, MSME businesses in this village are hampered by knowledge of online media. they find it difficult to use digital marketing. During this marketing system, they only go offline by leaving their goods at the shop or by calling if someone wants to order. Therefore, external assistance is needed to improve the community's ability to manage MSMEs. Based on this phenomenon, the KKN group decided to provide outreach to these MSMEs after observing and discussing with the community and the Pematang Jering MSMEs. The aim is to make it easier for people to use digital platforms. This outreach has proven effective in increasing public knowledge and interest in marketing their products. This socialization program results in people understanding and experiencing the usefulness and enjoyment of using digital platforms and providing great opportunities for businesses in the village to become more advanced.